2013
DOI: 10.1161/circulationaha.113.001340
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of Calpain3 Expression to the Skeletal Muscle Prevents Cardiac Toxicity and Corrects Pathology in a Murine Model of Limb-Girdle Muscular Dystrophy

Abstract: All vectors were constructed by classical molecular biology techniques (see online-only Data Supplement Methods). Plasmid DNA was prepared by using the Maxiprep 500 EF kit (Macherey Nagel), Background-Genetic defects in calpain3 (CAPN3) lead to limb-girdle muscular dystrophy type 2A, a disease of the skeletal muscle that affects predominantly the proximal limb muscles. We previously demonstrated the potential of adeno-associated virus-mediated transfer of the CAPN3 gene to correct the pathological signs in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 25 publications
5
51
0
2
Order By: Relevance
“…Briefly, LGMD2A is a skeletal muscle disease due to loss of calpain-3, an intracellular protease encoded by the CAPN3 gene that is predominantly expressed in skeletal muscle. The intravenous injection of a rAAV9 vector containing CAPN3 driven by a pan-muscle-specific promoter in mice caused severe fibrosis in heart and mortality, which was related to the transduction in heart and unregulated proteolytic activity of calpain-3 therein [76]. To prevent the detrimental effects related to both off-target and prolonged transgene expression, a number of strategies have been developed to regulate gene expression at both transcriptional and post-transcriptional levels.…”
Section: Raav Vector Design For Muscle-directed Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, LGMD2A is a skeletal muscle disease due to loss of calpain-3, an intracellular protease encoded by the CAPN3 gene that is predominantly expressed in skeletal muscle. The intravenous injection of a rAAV9 vector containing CAPN3 driven by a pan-muscle-specific promoter in mice caused severe fibrosis in heart and mortality, which was related to the transduction in heart and unregulated proteolytic activity of calpain-3 therein [76]. To prevent the detrimental effects related to both off-target and prolonged transgene expression, a number of strategies have been developed to regulate gene expression at both transcriptional and post-transcriptional levels.…”
Section: Raav Vector Design For Muscle-directed Gene Therapymentioning
confidence: 99%
“…Tissue-specific promoter and miRNA-based de-targeting design can be combined to further restrict transgene expression in muscle. In the LGMD2A study described at the beginning of this section, the authors developed new rAAV vectors that carry skeletal muscle-specific promoters and cardiac-specific miRNA-208a target sequence [76]. This vector design successfully suppressed calpain-3 expression in heart, thus preventing cardiac toxicity, and resulted in the correction of LGMD2A disease phenotype in skeletal muscle.…”
Section: Raav Vector Design For Muscle-directed Gene Therapymentioning
confidence: 99%
“…This study by Roudaut et al shows that cardiac toxicity from CAPN3 transgene expression can be successfully suppressed. Moreover, its expression in the skeletal muscles was sufficient to revert the myopathological signs of calpain 3 deficiency [16].…”
Section: Strategies For Treatmentmentioning
confidence: 98%
“…Many challenges lie ahead in translating promising therapeutic strategies into effective and accessible treatments but clinicians are optimistic that this is on the horizon. [16] evaluated the safety and efficacy of adeno-associated virus (AAV)-mediated calpain 3 gene transfer in a mouse model of LGMD2A using rAAV2/1 pseudotyped vectors and muscle-specific promoters to avoid calpain 3 cell toxicity more than a decade ago. They reported efficient and stable transgene expression in muscle with restoration of the proteolytic activity without evident toxicity, plus calpain 3 was correctly targeted to the sarcomere.…”
Section: Strategies For Treatmentmentioning
confidence: 99%
“…Further study implicated both increased protein aggregation and myofibrillar disintegration; the later mediated through an interaction with BAG3. Isabelle Richard (Généthon), organizer of the session, showed that adenoviral mediated calpain-3 gene therapy rescued skeletal muscle defect in calpain-3 deficient mice, but resulted in cardiotoxicity [75, 76]. Promoter and miR driven selective skeletal muscle expression eliminated the cardiac defects.…”
Section: Introductionmentioning
confidence: 99%